Composite positive electrode active material, positive electrode and lithium battery using the same, and manufacturing method thereof

By using lithium transition metal oxide cores and carbon-based material shell structures of different particle sizes in the positive electrode active material of lithium battery, the side reaction problems of nickel-based materials are solved, and the high-temperature cycle characteristics and energy density of lithium batteries are improved.

JP7628193B2Active Publication Date: 2025-02-07SAMSUNG SDI CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023573193
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-08
Filing Date
2022-06-07
Publication Date
2025-02-07
Estimated Expiration
2042-06-07

AI Technical Summary

Technical Problem

The existing nickel-based positive electrode active materials have reduced life characteristics and insufficient thermal stability in lithium batteries due to side reactions, which affects battery performance.

Method used

Using a composite positive electrode active material containing the first and second lithium transition metal oxides, electron and ion conductivity are improved by forming different particle sizes on its core and the shell structure containing the carbon-based material, and electrolyte contact is blocked through the carbon-based material to suppress side reactions.

Benefits of technology

It improves the high-temperature cycling characteristics of lithium batteries, suppresses the increase in internal resistance, and improves energy density and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628193000004
    Figure 0007628193000004
  • Figure 0007628193000001
    Figure 0007628193000001
  • Figure 0007628193000002
    Figure 0007628193000002
Patent Text Reader

Abstract

The present invention includes a first core including a first lithium transition metal oxide, a second core including a second lithium transition metal oxide, and a shell disposed along a surface of at least one of the first core and the second core, the shell being represented by the chemical formula M a O b (0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite positive electrode active material, a positive electrode and a lithium battery employing the same, and a method for manufacturing the same. [Background technology]

[0002] In order to meet the trend of miniaturization and high performance of various devices, importance is being placed on not only miniaturization and weight reduction of lithium batteries but also on high energy density, i.e., high capacity lithium batteries are becoming important.

[0003] In order to realize a lithium battery that meets the above-mentioned applications, positive electrode active materials having high capacity are being investigated.

[0004] Conventional nickel-based positive electrode active materials suffer from reduced life characteristics due to side reactions and also have poor thermal stability.

[0005] Therefore, a method is required that can prevent deterioration of battery performance while containing a nickel-based positive electrode active material. Summary of the Invention [Problem to be solved by the invention]

[0006] One aspect is to provide a novel composite positive electrode active material that can suppress side reactions of the composite positive electrode active material and improve the reversibility of the electrode reaction to prevent deterioration of lithium performance.

[0007] Another aspect is to provide a cathode comprising the composite cathode active material.

[0008] Yet another aspect is to provide a lithium battery employing the positive electrode.

[0009] Yet another aspect is to provide a method for making the composite positive electrode active material. [Means for solving the problem]

[0010] On one side, a first core containing a first lithium transition metal oxide, a second core containing a second lithium transition metal oxide, and a shell disposed along the surface of one or more of the first core and the second core, wherein the shell contains one or more first metal oxides represented by the chemical formula M a O b (0 < a ≤ 3, 0 < b < 4; if a is 1, 2, or 3, then b is not an integer) and a carbon-based material, wherein the first metal oxide is disposed within a carbon-based material matrix, and M is one or more metals selected from Groups 2 to 13, 15, and 16 of the Periodic Table of the Elements, A composite cathode active material is provided, wherein the first lithium transition metal oxide and the second lithium transition metal oxide have different average particle sizes from each other.

[0011] On another side, a cathode containing the composite cathode active material is provided.

[0012] On yet another side, a lithium battery containing the cathode is provided.

[0013] On yet another side, providing a first lithium transition metal oxide, providing a second lithium transition metal oxide, providing a composite, preparing one or more of a first core / shell structure obtained by mechanically milling the first lithium transition metal oxide and the composite, and a second core / shell structure obtained by mechanically milling the second lithium transition metal oxide and the composite, mixing the first core / shell structure with the second lithium transition metal oxide, or mixing the second core / shell structure with the first lithium transition metal oxide, or mixing the first core / shell structure with the second core / shell structure, wherein the composite is represented by the chemical formula M a Ob (0 < a ≤ 3, 0 < b < 4, and if a is 1, 2, or 3, then b is not an integer), including one or more first metal oxides and a carbon-based material, A method for manufacturing a composite cathode active material is provided, wherein the first metal oxide is disposed within a carbon-based material matrix, and M is one or more metals selected from Groups 2 to 13, 15, and 16 of the Periodic Table of the Elements.

Advantages of the Invention

[0014] According to one aspect, by disposing a shell containing a first metal oxide and a carbon-based material on one or more cores of a large-diameter lithium transition metal oxide and a small-diameter lithium transition metal oxide, the high-temperature cycle characteristics of a lithium battery are improved, and an increase in internal resistance is suppressed.

Brief Description of the Drawings

[0015] [Figure 1] It is a schematic diagram of a lithium battery according to a specific example.

Modes for Carrying Out the Invention

[0016] The present inventive concept described below can be subjected to various transformations and can have various embodiments. Specific embodiments are illustrated in the drawings and will be described in detail in the detailed description. However, this is not intended to limit the present inventive concept to specific embodiments, and it should be understood to include all transformations, equivalents, or alternatives included in the technical scope of the present inventive concept.

[0017] The terms used below are merely used to describe specific embodiments and are not intended to limit the technical idea. A singular expression includes a plural expression unless the context clearly indicates a different meaning. In the following, the terms "include" or "have" are intended to indicate the presence of a feature, number, step, operation, component, part, ingredient, material, or combination thereof described in the specification, and should be understood not to preclude the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, ingredients, materials, or combinations thereof. The " / " used below can be interpreted as "and" or "or" depending on the situation.

[0018] In the drawings, thicknesses of various layers and regions are exaggerated or reduced for clarity. Similar parts are designated by the same reference numerals throughout the specification. Throughout the specification, when a part, such as a layer, film, region, plate, etc., is referred to as being "on" or "above" another part, this includes not only when it is directly on top of the other part, but also when there is another part in between. Throughout the specification, terms such as first, second, etc. are used to describe various components, but the components should not be limited by the terms. The terms are used only to distinguish one component from another.

[0019] In this specification, the "particle size" of a particle refers to the average diameter when the particle is spherical, and refers to the average major axis length when the particle is non-spherical. The particle size is measured using a particle size analyzer (PSA). The "particle size" of a particle is, for example, the average particle size. The average particle size is, for example, the median particle size (D50). The median particle size (D50) is, for example, the particle size corresponding to the 50% cumulative volume calculated from the particle side having a small particle size in the particle size distribution measured by a laser diffraction method.

[0020] Hereinafter, the composite cathode active material according to exemplary specific examples, the cathode containing the same, the lithium battery, and the manufacturing method thereof will be described in more detail.

[0021] The composite cathode active material includes a first core containing a first lithium transition metal oxide, a second core containing a second lithium transition metal oxide, and a shell disposed along the surface of one or more of the first core and the second core, and the shell has the chemical formula M a O b (0 < a ≤ 3, 0 < b < 4; if a is 1, 2, or 3, then b is not an integer) and includes one or more first metal oxides and a carbon-based material, the first metal oxide is disposed within the carbon-based material matrix, M is one or more metals selected from Groups 2 to 13, 15, and 16 of the periodic table of elements, and the first lithium transition metal oxide and the second lithium transition metal oxide have different average particle sizes from each other.

[0022] Hereinafter, the theoretical basis for the excellent effects provided by the composite cathode active material according to a specific example will be described. This is for the purpose of assisting the understanding of the technical idea of the present invention and is not intended to limit the technical idea in any way.

[0023] The carbon-based conductive material is disposed in the gap between the positive electrode active materials, so that the electronic conductivity of the positive electrode can be improved. However, since the conductive material does not have ionic conductivity, the ionic conductivity of the positive electrode can be reduced. The greater the thickness of the positive electrode active material layer, the greater the reduction in the ionic conductivity of the positive electrode. As a result, the performance of a lithium battery using such a positive electrode can be significantly reduced. Meanwhile, the composite positive electrode active material includes a first core corresponding to a first lithium transition metal oxide and a second core corresponding to the second lithium transition metal oxide, and the first cores have different particle sizes, so that the second cores can be disposed in the gap between the first cores, or the first cores can be disposed in the gap between the second cores. Therefore, by further disposing other core particles in the gap between the core particles, the ionic conductivity of the positive electrode including such a composite positive electrode active material can be improved. In addition, since the shell of the core particle includes a carbon-based material, by further disposing other core particles in the gap between the core particles, the electronic conductivity of the positive electrode including the composite positive electrode active material can be improved. As a result, the high-temperature cycle characteristics of a lithium battery including such a composite positive electrode active material can be improved and an increase in internal resistance can be suppressed. In addition, by further disposing other core particles in the gaps between the core particles, the energy density of a lithium battery including the composite positive electrode active material can be further improved.

[0024] Conventional carbon-based materials are easily agglomerated, making it difficult to uniformly coat the core. On the other hand, the present composite positive electrode active material uses a composite containing a plurality of first metal oxides arranged in a carbon-based material matrix, and a uniform shell is arranged on the first core and / or the second core while preventing the carbon-based material from agglomerating. Therefore, by effectively blocking contact between the core and the electrolyte, side reactions due to contact between the core and the electrolyte are prevented. In addition, the generation of a resistance layer is suppressed by suppressing cation mixing by the electrolyte. In addition, the elution of transition metal ions is also suppressed. The carbon-based material is, for example, a crystalline carbon-based material. The carbon-based material is, for example, a carbon-based nanostructure. The carbon-based material is, for example, a carbon-based two-dimensional nanostructure. For example, the carbon-based material is graphene. In this case, the shell containing graphene and / or the matrix has flexibility, and therefore easily accepts the volume change of the composite positive electrode active material during charging and discharging, thereby suppressing the occurrence of cracks inside the composite positive electrode active material. Graphene has high electronic conductivity, which reduces the interfacial resistance between the composite positive electrode active material and the electrolyte, and therefore the internal resistance of the lithium battery is maintained or reduced despite the introduction of a graphene-containing shell.

[0025] The carbonaceous material contained in the shell of the composite positive electrode active material is derived from a graphene matrix, and therefore has a relatively low density and a high porosity compared to conventional carbonaceous materials derived from graphite-based materials. The d002 interplanar distance of the carbonaceous material contained in the shell of the composite positive electrode active material is, for example, 3.38 Å or more, 3.40 Å or more, 3.45 Å or more, 3.50 Å or more, 3.60 Å or more, 3.80 Å or more, or even 4.00 Å or more. The d002 interplanar distance of the carbonaceous material contained in the shell of the composite positive electrode active material is, for example, 3.38 to 4.0 Å, 3.38 to 3.8 Å, 3.38 to 3.6 Å, 3.38 to 3.5 Å, or even 3.38 to 3.45 Å. On the other hand, the d002 interplanar distance of conventional carbon-based materials derived from graphite-based materials is, for example, 3.38 Å or less, or even 3.35 to 3.38 Å.

[0026] The first metal oxide has a voltage resistance, and therefore can prevent the deterioration of the lithium transition metal oxide contained in the core during charging and discharging at high voltages. The shell contains, for example, one type of first metal oxide or two or more types of first metal oxides different from each other. As a result, the high-temperature cycle characteristics of a lithium battery containing the above-mentioned composite positive electrode active material are improved.

[0027] In the composite positive electrode active material, the content of the shell is, for example, 0.5 wt% to 3 wt%, 0.5 wt% to 2.5 wt%, 0.5 wt% to 2 wt%, or 0.5 wt% to 1.5 wt% of the total weight of the composite positive electrode active material. The content of the first metal oxide is, for example, 0.3 wt% to 1.8 wt%, 0.3 wt% to 1.5 wt%, 0.3 wt% to 1.2 wt%, or 0.3 wt% to 0.9 wt% of the total weight of the composite positive electrode active material. When the composite positive electrode active material contains the shell and the first metal oxide in such a content range, the cycle characteristics of the lithium battery are further improved.

[0028] In the composite positive electrode active material, for example, the particle size of the first lithium transition metal oxide is large and is larger than the particle size of the second lithium transition metal oxide. For example, the first lithium transition metal oxide is a lithium transition metal oxide having a large particle size. The particle size is, for example, an average particle size.

[0029] In the composite positive electrode active material, for example, the particle size of the second lithium transition metal oxide is small and smaller than the particle size of the first lithium transition metal oxide. For example, the second lithium transition metal oxide is a lithium transition metal oxide having a small particle size. The particle size is, for example, an average particle size.

[0030] In the composite positive electrode active material, for example, the first lithium transition metal oxide is a lithium transition metal oxide with a large diameter, and the second lithium transition metal oxide is also a lithium transition metal oxide with a small diameter. That is, the first core is a lithium transition metal oxide with a large diameter, and the second core is a lithium transition metal oxide with a small diameter. For example, a second core having a smaller average particle size than the first core may be disposed in the gap between the first cores. By disposing the second core particles, which are small diameter particles, in the gap between the first core particles, which are large diameter particles, the ionic conductivity and electronic conductivity of the positive electrode including the composite positive electrode active material may be improved at the same time. In addition, the energy density of the positive electrode including the composite positive electrode active material may be improved. As a result, the energy density of the lithium battery including the composite positive electrode active material may be improved, and the cycle characteristics may be improved.

[0031] The first lithium transition metal oxide and the second lithium transition metal oxide may have, for example, a bimodal particle size distribution in a particle size distribution diagram. For example, the composite positive electrode active material may have a bimodal particle size distribution having two peaks in a particle size distribution diagram obtained using a particle size analyzer (PSA), etc. The bimodal particle size distribution has a first peak corresponding to the first lithium transition metal oxide and a second peak corresponding to the second lithium transition metal oxide.

[0032] The average particle size of the first lithium transition metal oxide is, for example, more than 10 μm to 25 μm, 11 μm to 20 μm, 12 μm to 20 μm, 12 μm to 19 μm, or 15 μm to 19 μm. The average particle size of the first lithium transition metal oxide is, for example, a median particle size (D50). The average particle size of the second lithium transition metal oxide is, for example, 1 μm to 10 μm, 2 μm to 10 μm, 2 μm to 9 μm, 2 μm to 8 μm, or 2 μm to 6 μm. The average particle size of the first lithium transition metal oxide is, for example, a median particle size (D50). When the first lithium transition metal oxide and the second lithium transition metal oxide have average particle sizes in such ranges, the energy density and / or cycle characteristics of a lithium battery including the composite positive electrode active material can be further improved.

[0033] The average particle size of the first lithium transition metal oxide and the second lithium transition metal oxide is measured, for example, using a measuring device of a laser diffraction method or a dynamic light scattering method. The average particle size is measured, for example, using a laser scattering particle size distribution meter (for example, HORIBA LA-920), and is the value of the median particle size (D50) when 50% is accumulated from the small particle side in volume conversion.

[0034] The weight ratio of the first lithium transition metal oxide to the second lithium transition metal oxide is, for example, 90:10 to 60:40, 85:15 to 65:35, 80:20 to 65:35, or 75:25 to 65:35. When the first lithium transition metal oxide to the second lithium transition metal oxide have a weight ratio in such a range, the energy density and / or cycle characteristics of a lithium battery including the composite positive electrode active material can be further improved.

[0035] In the composite positive electrode active material, for example, the shell may be disposed only on the first core. That is, the shell may be disposed on the first core, but not on the second core. For example, the shell may be disposed on the first lithium transition metal oxide, which is a lithium transition metal oxide having a large diameter, but not on the second lithium transition metal oxide, which is a lithium transition metal oxide having a small diameter. By disposing the shell on the first core, a first core / shell structure is obtained. By including the first core / shell structure and the second core in the composite positive electrode active material, the energy density and / or cycle characteristics of the lithium battery may be further improved.

[0036] In the composite positive electrode active material, for example, the shell may be disposed only on the second core. That is, the shell may be disposed on the second core, but not on the first core. For example, the shell may be disposed on the second lithium transition metal oxide, which is a lithium transition metal oxide with a small diameter, but not on the first lithium transition metal oxide, which is a lithium transition metal oxide with a large diameter. By disposing the shell on the second core, a second core / shell structure is obtained. By including the second core / shell structure and the first core in the composite positive electrode active material, the energy density and / or cycle characteristics of the lithium battery may be further improved.

[0037] In the composite positive electrode active material, for example, a shell may be disposed on both the first core and the second core. That is, a shell may be disposed on the first core and at the same time on the second core. For example, a shell may be disposed on the first lithium transition metal oxide, which is a lithium transition metal oxide with a large diameter, and on the second lithium transition metal oxide, which is a lithium transition metal oxide with a small diameter. By disposing the shell on the first core, a first core / shell structure is obtained, and by disposing the shell on the second core, a second core / shell structure is obtained. When the composite positive electrode active material includes both the first core / shell structure and the second core / shell structure, the energy density and / or cycle characteristics of the lithium battery may be further improved.

[0038] The metal contained in the first metal oxide is, for example, AlOz (0 < z < 3), NbO x (0 < x < 2.5), MgO x (0 < x < 1), Sc2O z (0 < z < 3), TiO y (0 < y < 2), ZrO y (0 < y < 2), V2O z (0 < z < 3), WO y (0 < y < 2), MnO y (0 < y < 2), Fe2O z (0 < z < 3), Co3O w (0 < w < 4), PdO x (0 < x < 1), CuO x (0 < x < 1), AgO x (0 < x < 1), ZnO x (0 < x < 1), Sb2O z (0 < z < 3), and SeO y (0 < y < 2) and is also one or more selected therefrom. By disposing such a first metal oxide within the carbon-based material matrix, the uniformity of the shell disposed on the core is improved, and the voltage resistance of the composite cathode active material is further improved. For example, the shell contains Al2O as the first metal oxide x (0 < x < 3).

[0039] The shell has the chemical formula M a O cIt further contains one or more second metal oxides represented by (0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, c is an integer). The M is one or more metals selected from Groups 2 to 13, 15, and 16 of the periodic table of the elements. For example, the second metal oxide contains the same metal as the first metal oxide, and c / a, which is the ratio of c to a of the second metal oxide, has a value larger than b / a, which is the ratio of b to a of the first metal oxide. For example, c / a > b / a. The second metal oxide is selected from, for example, Al2O3, NbO, NbO2, Nb2O5, MgO, Sc2O3, TiO2, ZrO2, V2O3, WO2, MnO2, Fe2O3, Co3O4, PdO, CuO, AgO, ZnO, Sb2O3, and SeO2. The first metal oxide is a reduction product of the second metal oxide. The first metal oxide is obtained by reducing part or all of the second metal oxide. Therefore, the first metal oxide has a lower oxygen content and a higher oxidation number of the metal than the second metal oxide. For example, the shell is the first metal oxide Al2O x It contains (0 < x < 3) and Al2O3 which is a second metal oxide.

[0040] Hereinafter, unless otherwise specified, "core" is interpreted as a term including one or more of "first core" and "second core".

[0041] Hereinafter, unless otherwise specified, "lithium transition metal oxide" is interpreted as a term including one or more of "first lithium transition metal oxide" and "second lithium transition metal oxide".

[0042] In the composite cathode active material, for example, the transition metal of the carbon-based material contained in the shell and the lithium transition metal oxide contained in the core are chemically bonded through a chemical bond.

[0043] The carbon atom (C) of the carbon-based material contained in the shell and the transition metal (Me) of the lithium transition metal oxide are chemically bound through, for example, a CO-Me bond (e.g., CO-Ni bond or CO-Co bond) via an oxygen atom. The carbon-based material contained in the shell and the lithium transition metal oxide contained in the core are chemically bound through a chemical bond, thereby forming a composite of the core and shell. Therefore, it is distinguished from a simple physical mixture of the carbon-based material and the lithium transition metal oxide.

[0044] The first metal oxide and the carbon-based material contained in the shell are also chemically bound through a chemical bond. Here, the chemical bond is, for example, a covalent bond or an ionic bond. The covalent bond is, for example, a bond including at least one of an ester group, an ether group, a carbonyl group, an amide group, a carbonate anhydride group, and an acid anhydride group. The ionic bond is, for example, a bond including a carboxylate ion, an ammonium ion, an acyl cation group, or the like.

[0045] The thickness of the shell is, for example, 1 nm to 5 μm, 1 nm to 1 μm, 1 nm to 500 nm, 1 nm to 200 nm, 1 nm to 100 nm, 1 nm to 90 nm, 1 nm to 80 nm, 1 nm to 70 nm, 1 nm to 60 nm, 1 nm to 50 nm, 1 nm to 40 nm, 1 nm to 30 nm, or 1 nm to 20 nm. When the shell has a thickness in such a range, the conductivity of the electrode containing the composite positive electrode active material is improved.

[0046] The composite positive electrode active material may further include, for example, a third metal doped on the core or a third metal oxide coated on the core. The shell may then be disposed on the doped third metal or the coated third metal oxide. For example, the surface of the lithium transition metal oxide included in the core may be doped with a third metal, or the surface of the lithium transition metal oxide may be coated with a third metal oxide, and then the shell may be disposed on the third metal and / or the third metal oxide. For example, the composite positive electrode active material may include a core, an intermediate layer disposed on the core, and a shell disposed on the intermediate layer, and the intermediate layer may include a third metal or a third metal oxide. The third metal may be one or more metals selected from Al, Zr, W, and Co, and the third metal oxide may be Al2O3, Li2O-ZrO2, WO2, CoO, Co2O3, Co3O4, etc.

[0047] The shell included in the composite positive electrode active material includes at least one selected from a composite including a first metal oxide and a carbon-based material, such as graphene, and a milling result of the composite, in which the first metal oxide is disposed in a matrix of the carbon-based material, such as a graphene matrix. The shell is prepared, for example, from a composite including a first metal oxide and a carbon-based material, such as graphene. The composite further includes a second metal oxide in addition to the first metal oxide. The composite includes, for example, two or more kinds of the first metal oxide. The composite may include, for example, two or more kinds of the first metal oxide and two or more kinds of the second metal oxide.

[0048] The content of one or more of the composite and milling products thereof included in the composite positive electrode active material may be, for example, 3 wt% or less, 2 wt% or less, 1 wt% or less, or 0.5 wt% or less of the total weight of the composite positive electrode active material. The content of one or more of the composite and milling products thereof may be 0.01 wt% to 3 wt%, 0.01 wt% to 1 wt%, 0.01 wt% to 0.7 wt%, or 0.01 wt% to 0.5 wt% of the total weight of the composite positive electrode active material. When the composite positive electrode active material includes one or more of the composite and milling products thereof within such ranges, the cycle characteristics of a lithium battery including the composite positive electrode active material are further improved.

[0049] The content of one or more of the composite and milling products thereof contained in the first core / shell structure may be, for example, 3 wt% or less, 2 wt% or less, 1 wt% or less, or 0.5 wt% or less of the total weight of the first core / shell structure. The content of one or more of the composite and milling products thereof may be 0.01 wt% to 3 wt%, 0.01 wt% to 1 wt%, 0.01 wt% to 0.7 wt%, or 0.01 wt% to 0.5 wt% of the total weight of the first core / shell structure. When the first core / shell structure contains one or more of the composite and milling products thereof in such a range, the cycle characteristics of a lithium battery including the composite positive electrode active material are further improved.

[0050] The content of one or more of the composite and milling products thereof contained in the second core / shell structure may be, for example, 3 wt% or less, 2 wt% or less, 1 wt% or less, or 0.5 wt% or less of the total weight of the second core / shell structure. The content of one or more of the composite and milling products thereof may be 0.01 wt% to 3 wt%, 0.01 wt% to 1 wt%, 0.01 wt% to 0.7 wt%, or 0.01 wt% to 0.5 wt% of the total weight of the second core / shell structure. When the second core / shell structure contains one or more of the composite and milling products thereof in such a range, the cycle characteristics of a lithium battery including the composite positive electrode active material are further improved.

[0051] The average particle size of one or more selected from the first metal oxide and the second metal oxide contained in the composite may be 1 nm to 1 μm, 1 nm to 500 nm, 1 nm to 200 nm, 1 nm to 100 nm, 1 nm to 70 nm, 1 nm to 50 nm, 1 nm to 30 nm, 3 nm to 30 nm, 3 nm to 25 nm, 5 nm to 25 nm, 5 nm to 20 nm, 7 nm to 20 nm, or 7 nm to 15 nm. The first metal oxide and / or the second metal oxide may have such a nano-range particle size, so that they can be more uniformly distributed in the carbon-based material matrix of the composite. Therefore, such a composite may be uniformly coated on the core without agglomeration to form a shell. In addition, the first metal oxide and / or the second metal oxide may have such a particle size range, so that they can be more uniformly arranged on the core.

[0052] Therefore, by uniformly disposing the first metal oxide and / or the second metal oxide on the core, the voltage resistance characteristics can be more effectively exhibited.

[0053] The average particle size of the first metal oxide and the second metal oxide is measured, for example, using a measuring device of the laser diffraction method or the dynamic light scattering method. The average particle size is measured, for example, using a laser scattering particle size distribution meter (e.g., HORIBA LA-920), and is the median particle size (D50) value when 50% is accumulated from the small particle side in volume conversion.

[0054] The composite may contain one or more selected from the first metal oxide and the second metal oxide with a uniformity deviation of 3% or less, 2% or less, or 1% or less. The uniformity may be measured, for example, by XPS. Thus, the composite may contain one or more selected from the first metal oxide and the second metal oxide with a uniform distribution with a deviation of 3% or less, 2% or less, or 1% or less.

[0055] The carbon-based material included in the composite may have, for example, a branched structure, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the branched structure of the carbon-based material. The branched structure of the carbon-based material may include, for example, a plurality of carbon-based material particles that are in contact with each other. The branched structure of the carbon-based material may provide a variety of conductive paths.

[0056] The carbon-based material included in the composite may be, for example, graphene. The graphene may have, for example, a branched structure, and one or more metal oxides selected from a first metal oxide and a second metal oxide may be distributed in the branched structure of the graphene. The branched structure of the graphene may include, for example, a plurality of graphene particles that are in contact with each other. The branched structure of the graphene may provide various conductive paths.

[0057] The carbon-based material contained in the composite may have, for example, a spherical structure, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure. The size of the spherical structure of the carbon-based material may be 50 nm to 300 nm. There may be a plurality of carbon-based materials having a spherical structure. Since the carbon-based material has a spherical structure, the composite may have a robust structure.

[0058] The carbon-based material contained in the composite may be, for example, graphene. The graphene may have, for example, a spherical structure, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structure. The size of the spherical structure of graphene may be 50 nm to 300 nm. There may be a plurality of graphenes having a spherical structure. Since the graphene has a spherical structure, the composite may have a robust structure.

[0059] The carbon-based material contained in the composite has, for example, a spiral structure in which a plurality of spherical structures are connected, and one or more metal oxides selected from the first metal oxide and the second metal oxide may be distributed within the spherical structures of the spiral structure. The size of the spiral structure of the carbon-based material is 500 nm to 100 μm. Since the carbon-based material has a spiral structure, the composite can have a robust structure.

[0060] The carbon-based material contained in the composite may be, for example, graphene. The graphene may have a spiral structure in which a plurality of spherical structures are connected, and one or more metal oxides selected from a first metal oxide and a second metal oxide may be distributed within the spherical structures of the spiral structure. The size of the spiral structure of graphene may be 500 nm to 100 μm. Since the graphene has a spiral structure, the composite may have a robust structure.

[0061] The carbon-based material contained in the composite may have a cluster structure in which a plurality of spherical structures are aggregated, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed within the spherical structures of the cluster structure. The size of the cluster structure of the carbon-based material is 0.5 mm to 10 cm. Since the carbon-based material has a cluster structure, the composite may have a robust structure.

[0062] The carbon-based material included in the composite may be, for example, graphene. The graphene may have a cluster structure in which a plurality of spherical structures are aggregated, and at least one metal oxide selected from the first metal oxide and the second metal oxide may be distributed within the spherical structures of the cluster structure. The size of the graphene cluster structure may be 0.5 mm to 10 cm. As the graphene has a cluster structure, the composite may have a robust structure.

[0063] The composite may be, for example, a wrinkled faceted-ball structure, and one or more selected from the first metal oxide and the second metal oxide may be distributed inside or on the surface of the structure. The composite may be easily coated on the irregular surface irregularities of the core by such a faceted-ball structure.

[0064] The composite may be, for example, a planar structure, and one or more selected from the first metal oxide and the second metal oxide may be distributed inside or on the surface of the structure. Such a two-dimensional planar structure allows the composite to be easily coated on the irregular surface irregularities of the core.

[0065] The carbonaceous material contained in the composite extends in the first metal oxide a distance of 10 nm or less and includes at least 1 to 20 carbonaceous material layers. For example, a carbonaceous material having a total thickness of 12 nm or less can be disposed on the first metal oxide by stacking multiple carbonaceous material layers. For example, the total thickness of the carbonaceous material can be 0.6 to 12 nm.

[0066] The carbonaceous material contained in the composite may be, for example, graphene. The graphene extends in the first metal oxide for a distance of 10 nm or less and includes at least 1 to 20 graphene layers. For example, a plurality of graphene layers may be stacked to provide graphene having a total thickness of 12 nm or less on the first metal oxide. For example, the total thickness of the graphene may be 0.6 to 12 nm.

[0067] The first core and / or the second core included in the composite positive electrode active material contains, for example, a lithium transition metal oxide represented by the following Chemical Formula 1:

[0068] <Chemical Formula 1> Li a Co x M y O 2-b A b

[0069] In the Chemical Formula 1, 1.0 ≦ a ≦ 1.2, 0 ≦ b ≦ 0.2, 0.9 ≦ x ≦ 1, 0 ≦ y ≦ 0.1, and x + y = 1, M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and A is F, S, Cl, Br, or a combination thereof.

[0070] The first core and / or the second core included in the composite positive electrode active material contains, for example, a lithium transition metal oxide represented by the following Chemical Formulas 2 to 4:

[0071] <Chemical Formula 2> LiNi x Co y Mn z O2

[0072] <Chemical Formula 3> LiNi x Co y Al z O2

[0073] In the Chemical Formulas 2 and 3, 0.8 ≦ x ≦ 0.95, 0 < y ≦ 0.2, 0 < z ≦ 0.2, and x + y + z = 1.

[0074] <Chemical Formula 4> LiNi x Coy Mn z Al w O2

[0075] In Chemical Formula 4, 0.8 ≦ x ≦ 0.95, 0 < y ≦ 0.2, 0 < z ≦ 0.2, 0 < w ≦ 0.2, and x + y + z + w = 1.

[0076] The lithium transition metal oxides of Chemical Formulas 1 to 4 can provide excellent initial capacity, normal temperature life characteristics, and high temperature life characteristics while having a high nickel content of 80 mol% or more, 85 mol% or more, or 90 mol% or more based on the total number of moles of transition metals. For example, the nickel content in the lithium transition metal oxides of Chemical Formulas 1 to 4 is 80 mol% to 95 mol%, 85 mol% to 95 mol%, or 90 mol% to 95 mol% based on the total number of moles of transition metals.

[0077] The first core and / or the second core included in the composite positive electrode active material contains, for example, a lithium transition metal oxide represented by the following Chemical Formulas 5 to 6:

[0078] <Chemical formula a Co x MyO 2-b A b

[0079] In Chemical Formula 5, 1.0 ≦ a ≦ 1.2, 0 ≦ b ≦ 0.2, 0.9 ≦ x ≦ 1, 0 ≦ y ≦ 0.1, and x + y = 1, M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof, and A is F, S, Cl, Br, or a combination thereof.

[0080] <Chemical formula 6> LiCoO2

[0081] According to another embodiment, the positive electrode includes the composite positive electrode active material described above. The positive electrode includes the composite positive electrode active material described above, which provides improved cycle characteristics and increased conductivity.

[0082] The positive electrode can be produced, for example, by the following exemplary method, but is not necessarily limited to such a method, and can be adjusted according to required conditions.

[0083] First, the composite positive active material, conductive material, binder, and solvent are mixed to prepare a positive active material composition. The prepared positive active material composition is directly coated on an aluminum current collector and dried to manufacture a positive electrode plate having a positive active material layer. Alternatively, the positive active material composition is cast on a separate support, and then peeled off from the support to obtain a film, which is then laminated on the aluminum current collector to manufacture a positive electrode plate having a positive active material layer.

[0084] Examples of the conductive material include carbon black, graphite particles, natural graphite, artificial graphite, acetylene black, ketjen black, carbon fibers, carbon nanotubes, metal powders or metal fibers or metal tubes such as copper, nickel, aluminum, and silver, and conductive polymers such as polyphenylene derivatives, but are not limited thereto, and any material used as a conductive material in the art can be used. Alternatively, the positive electrode may not include a separate conductive material, for example. Examples of the binder include vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polytetrafluoroethylene (PTFE), a mixture of the above-mentioned polymers, and styrene butadiene rubber-based polymers, and examples of the solvent include N-methylpyrrolidone (NMP), acetone, and water, but are not limited thereto, and any material used as a conductive material in the art can be used.

[0085] It is also possible to further add a plasticizer or pore-forming agent to the positive electrode active material composition to form pores inside the electrode plate.

[0086] The contents of the composite positive electrode active material, conductive material, binder, and solvent used in the positive electrode are at levels typically used in lithium batteries. Depending on the application and configuration of the lithium battery, one or more of the conductive material, binder, and solvent may be omitted.

[0087] The positive electrode contains a binder in an amount of 0.1 to 10 wt % or 0.1 to 5 wt % of the total weight of the positive electrode active material layer. The positive electrode contains a composite positive electrode active material in an amount of 90 to 99 wt % or 95 to 99 wt % of the total weight of the positive electrode active material layer.

[0088] In addition, the positive electrode may further include other common positive electrode active materials in addition to the above-mentioned composite positive electrode active material.

[0089] The common positive electrode active material can be any lithium-containing metal oxide that is commonly used in the art, without any restrictions. For example, one or more of composite oxides of lithium and a metal selected from cobalt, manganese, nickel, and combinations thereof can be used. Specific examples of the composite oxides include Li a A 1-b B b D2 (wherein, 0.90≦a≦1, and 0≦b≦0.5); Li a E 1-b B b O 2-c D c (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05); LiE 2-b B b O 4-c D c (wherein, 0≦b≦0.5, 0≦c≦0.05); Li a Ni 1-b-c Co b B c D α (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Co b B c O 2-α F α(wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Co b B c O 2-α F2 (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B c D α (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b B c O 2-α F α (wherein, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B c O 2-α F2 (wherein, 0.90≦a≦1, 0≦b ≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O2 (wherein, 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, 0.001≦d≦0.1); Li a Ni b Co c Mn d GeO2 (wherein, 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, 0.001≦e≦0.1); Li a NiG b O2 (wherein, 0.90≦a≦1, 0.001≦b≦0.1); Li a CoG b O2 (wherein, 0.90≦a≦1, 0.001≦b≦0.1); Li a MnG b O2 (wherein, 0.90≦a≦1, 0.001≦b≦0.1); Li a Mn2G bO4 (wherein 0.90≦a≦1, 0.001≦b≦0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiIO2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) Any one of the compounds represented by the chemical formula Fe2(PO4)3(0≦f≦2);LiFePO4 can be used:

[0090] In the chemical formula representing the above-mentioned compound, A is Ni, Co, Mn, or a combination thereof; B is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof; D is O, F, S, P, or a combination thereof; E is Co, Mn, or a combination thereof; F is F, S, P, or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof; Q is Ti, Mo, Mn, or a combination thereof; I is Cr, V, Fe, Sc, Y, or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof.

[0091] It is also possible to use a compound in which a coating layer is added to the surface of the above-mentioned compound, and it is also possible to use a mixture of the above-mentioned compound and a compound to which a coating layer is added. The coating layer added to the surface of the above-mentioned compound includes, for example, a coating element compound such as an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of a coating element of a coating element. The compound forming such a coating layer is amorphous or crystalline. The coating element contained in the coating layer is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method of forming the coating layer is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spray coating, immersion, etc. A detailed description of the specific coating method is omitted because it is well understood by those skilled in the art.

[0092] A lithium battery according to yet another embodiment employs a positive electrode comprising the composite active positive electrode material described above.

[0093] The lithium battery employs a positive electrode containing the above-mentioned composite positive electrode active material, thereby providing improved cycle characteristics and thermal stability.

[0094] The lithium battery can be manufactured, for example, by the following exemplary method, but is not necessarily limited to such a method, and can be adjusted according to the required conditions.

[0095] First, the positive electrode is manufactured by the above-mentioned positive electrode manufacturing method.

[0096] Next, the negative electrode is prepared as follows. The negative electrode is prepared by substantially the same method as the positive electrode, except that, for example, a negative electrode active material is used instead of a composite positive electrode active material. In addition, in the negative electrode active material composition, the conductive material, the binder, and the solvent may be substantially the same as those of the positive electrode. For example, the negative electrode active material, the conductive material, the binder, and the solvent are mixed to prepare a negative electrode active material composition, which is directly coated on a copper current collector to prepare a negative electrode plate. Alternatively, the prepared negative electrode active material composition is cast on a separate support, and the negative electrode active material film peeled off from the support is laminated on a copper current collector to prepare a negative electrode plate.

[0097] The negative electrode active material may be any material known in the art for use as a negative electrode active material for lithium batteries, including, for example, at least one selected from the group consisting of lithium metal, metals capable of being alloyed with lithium, transition metal oxides, non-transition metal oxides, and carbonaceous materials.

[0098] Examples of metals that can be alloyed with lithium include Si, Sn, Al, Ge, Pb, Bi, Sb, Si-Y alloys (wherein Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, or a combination thereof, and is not Si), and Sn-Y alloys (wherein Y is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a transition metal, a rare earth element, or a combination thereof, and is not Sn). The element Y is, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof. The transition metal oxide is, for example, lithium titanium oxide, vanadium oxide, lithium vanadium oxide, or the like.

[0099] Non-transition metal oxides include, for example, SnO2, SiO x (0 <x<2)などである。

[0100] The carbon-based material is, for example, crystalline carbon, amorphous carbon, or a mixture thereof. The crystalline carbon is, for example, graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite. The amorphous carbon is, for example, soft carbon (low-temperature calcined carbon) or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0101] The contents of the negative electrode active material, conductive material, binder, and solvent are at levels typically used in lithium batteries, and one or more of the conductive material, binder, and solvent may be omitted depending on the application and configuration of the lithium battery.

[0102] The binder content of the negative electrode is, for example, 0.1 to 10 wt% or 0.1 to 5 wt% of the total weight of the negative electrode active material layer. The conductive material content of the negative electrode is, for example, 0.1 to 10 wt% or 0.1 to 5 wt% of the total weight of the negative electrode active material layer. The negative electrode active material content of the negative electrode is, for example, 90 wt% to 99 wt% or 95 wt% to 99 wt% of the total weight of the negative electrode active material layer.

[0103] When the negative electrode active material is lithium metal, the negative electrode may not include a binder and a conductive material.

[0104] Next, a separator is provided that is interposed between the positive electrode and the negative electrode.

[0105] The separator may be any of those commonly used in lithium batteries.

[0106] The separator used has low resistance to the ion movement of the electrolyte and excellent electrolyte moisture absorption. The separator is made of glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and is in the form of a nonwoven or woven fabric. A rollable separator such as polyethylene or polypropylene is used for a lithium ion battery, and an organic separator with excellent electrolyte impregnation is used for a lithium ion polymer battery.

[0107] The separator is manufactured by the following exemplary method, but is not necessarily limited to such method, and may be adjusted according to the required conditions.

[0108] First, a separator composition is prepared by mixing a polymer resin, a filler, and a solvent. The separator composition is directly coated on the top of an electrode and dried to form a separator. Alternatively, the separator composition is cast on a support and dried, and the separator film is peeled off from the support and laminated on the top of an electrode to form a separator.

[0109] The polymer used in the manufacture of the separator is not particularly limited, and any polymer that is used as a binder for electrode plates can be used, such as vinylidene fluoride / hexafluoropropylene copolymer, polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, or a mixture thereof.

[0110] The electrolyte is then prepared.

[0111] The electrolyte is, for example, an organic electrolyte solution, which is produced by dissolving a lithium salt in an organic solvent, for example.

[0112] The organic solvent can be any organic solvent used in the art. The organic solvent can be, for example, propylene carbonate, ethylene carbonate, fluoroethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, dibutyl carbonate, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, γ-butyrolactone, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethylsulfoxide, dioxane, 1,2-dimethoxyethane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, diethylene glycol, dimethyl ether, or a mixture thereof.

[0113] Any lithium salt that is used as a lithium salt in the art can be used. Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are each a natural number from 1 to 20), LiCl, LiI, or a mixture thereof.

[0114] Alternatively, the electrolyte is a solid electrolyte, such as, but not limited to, boron oxide, lithium oxynitride, or the like, and any solid electrolyte known in the art may be used.

[0115] The solid electrolyte may be formed on the negative electrode by a method such as sputtering, or a separate solid electrolyte sheet may be laminated on the negative electrode.

[0116] The solid electrolyte is, for example, an oxide-based solid electrolyte or a sulfide-based solid electrolyte.

[0117] The solid electrolyte is, for example, an oxide-based solid electrolyte. The oxide-based solid electrolyte is Li 1+x+y Al x Ti 2-x S y P 3-y O 12 (0 <x<2、0≦y<3)、BaTiO3、Pb(Zr、Ti)O3(PZT)、Pb 1-x La x Zr 1-y Ti y O3(PLZT)(O≦x<1, O≦y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3(PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2、0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2、0<y<1、0<z<3)、Li 1+x+y (Al, Ga) x (Ti, Ge) 2-x S y P 3-y O 12 (0≦x≦10≦y≦1), Li x La y TiO3(0 <x<2、0<y<3)、Li2O、LiOH、Li2CO3、LiAlO2、Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2、Li 3+x La3M2O 12 (M=Te, Nb, or Zr, x is an integer from 1 to 10). The solid electrolyte is produced by a sintering method or the like. For example, the oxide-based solid electrolyte is Li7La3Zr2O 12 (LLZO) and Li 3+x La3Zr 2-a M a O 12(M doped LLZO, M=Ga, W, Nb, Ta, or Al, x is an integer of 1 to 10) is a garnet-type solid electrolyte selected from the group consisting of:

[0118] The sulfide-based solid electrolyte includes, for example, lithium sulfide, silicon sulfide, phosphorus sulfide, boron sulfide, or a combination thereof. The sulfide-based solid electrolyte particles include Li2S, P2S5, SiS2, GeS2, B2S3, or a combination thereof. The sulfide-based solid electrolyte particles are also Li2S or P2S5. The sulfide-based solid electrolyte particles are known to have a higher lithium ion conductivity than other inorganic compounds. For example, the sulfide-based solid electrolyte includes Li2S and P2S5. When the sulfide solid electrolyte material constituting the sulfide-based solid electrolyte includes Li2S-P2S5, the mixed molar ratio of Li2S:P2S5 is, for example, in the range of about 50:50 to about 90:10. In addition, Li3PO4, halogen, halogen compound, Li 2+2x Zinc 1-x GeO4 (“LISICON”, 0≦x<1), Li 3+y PO 4-x N x( "LIPON", 0 <x<4、0<y<3)、Li 3.25 Ge 0.25 P 0.75 An inorganic solid electrolyte prepared by adding Li2S-P2S5, SiS2, GeS2, B2S3, or a combination thereof to an inorganic solid electrolyte may be used as the sulfide solid electrolyte. Non-limiting examples of sulfide solid electrolyte materials include Li2S-P2S5; Li2S-P2S5-LiX (X=halogen); Li2S-P2S5-Li2O; Li2S-P2S5-Li2O-LiI; Li2S-SiS2; Li2S-SiS2-LiI; Li2S-SiS2-LiBr; Li2S-SiS2-LiCl; Li2S-SiS2-B2S3-LiI; Li2S-SiS2-P2S5-LiI; Li2S-B2S3; Li2S-P2S5-Z m S n(0 < m < 10, 0 < n < 10, Z = Ge, Zn or Ga); Li2S - GeS2; Li2S - SiS2 - Li3PO4; and Li2S - SiS2 - Li p MO q (0 < p < 10, 0 < q < 10, M = P, Si, Ge, B, Al, Ga or In). In this regard, the sulfide - based solid electrolyte material can be manufactured by treating raw starting materials of the sulfide - based solid electrolyte substance (e.g., Li2S, P2S5, etc.) by a melt quenching method, a mechanical milling method, etc. Further, a calcinations process can be performed after the above treatment. The sulfide - based solid electrolyte can be amorphous, crystalline, or in a state where they are mixed.

[0119] As shown in FIG. 1, an exemplary lithium battery 1 includes a positive electrode 3, a negative electrode 2, and a separator 4. The positive electrode 3, the negative electrode 2, and the separator 4 are wound or folded and housed in a battery case 5. An organic electrolyte is injected into the battery case 5 and sealed by a cap assembly 6 to complete the lithium battery 1. The battery case 5 is cylindrical, but is not necessarily limited to such a form and may be, for example, rectangular, thin - film - like, etc.

[0120] A pouch - type lithium battery includes one or more battery structures. A separator is disposed between the positive electrode and the negative electrode to form a battery structure. After the battery structures are stacked by a bicell structure, they are impregnated with an organic electrolyte, housed and sealed in a pouch to complete the pouch - type lithium battery.

[0121] Multiple lithium batteries are stacked to form a battery module and / or a battery pack, and such battery modules and / or battery packs are used in all devices that require high capacity and high output. For example, they can be used in notebook computers, smartphones, electric vehicles, etc.

[0122] A lithium battery using a solid electrolyte is also a solid-state battery or an all-solid-state battery. A lithium battery using a solid electrolyte may have a solid electrolyte layer disposed between the positive electrode and the negative electrode instead of a separator. A lithium battery using a solid electrolyte may further include a solid electrolyte in one or more of the positive electrode and the negative electrode. For example, in a lithium battery in which an electrolyte layer containing a sulfide-based solid electrolyte is disposed between the positive electrode and the negative electrode, one or more of the positive electrode and the negative electrode may include a sulfide-based solid electrolyte.

[0123] Lithium batteries have excellent life characteristics and high rate characteristics, and are therefore used in, for example, electric vehicles (EVs) and energy storage systems (ESSs). For example, they are used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs). They are also used in fields that require the storage of large amounts of power, such as electric bicycles and power tools.

[0124] According to yet another embodiment, a method for preparing a composite positive electrode active material includes providing a first lithium metal oxide, providing a second lithium metal oxide, providing a composite, preparing one or more of a first core / shell structure obtained by mechanically milling the first lithium metal oxide and the composite and a second core / shell structure obtained by mechanically milling the second lithium metal oxide and the composite, and mixing the first core / shell structure with the second lithium metal oxide, mixing the second core / shell structure with the first lithium metal oxide, or mixing the first core / shell structure with the second core / shell structure, wherein the composite has a chemical formula M a O b(0 < a ≤ 3, 0 < b < 4, a is 1, 2, or 3, and b is not an integer) and one or more first metal oxides and a carbon-based material, wherein the first metal oxide is disposed within the carbon-based material matrix, and said M is one or more metals selected from Groups 2 to 13, 15, and 16 of the Periodic Table of the Elements. In the step of mechanically milling, the milling method is not particularly limited and is a method of bringing the lithium transition metal oxide into contact with the composite using a machine, and any method that can be used in the art can be used.

[0125] A first lithium transition metal oxide is provided. The first lithium transition metal oxide is, for example, a compound represented by Chemical Formulas 1 to 6 described above.

[0126] A second lithium transition metal oxide is provided. The second lithium transition metal oxide is, for example, a compound represented by Chemical Formulas 1 to 6 described above.

[0127] The step of providing the composite includes, for example, supplying a reaction gas composed of a carbon source gas to a structure containing a metal oxide and performing heat treatment to provide an undoped composite, and mixing the undoped composite with a fluorine (F)-containing compound to prepare the composite.

[0128] The step of providing the composite includes, for example, M a O c (0 < a ≤ 3, 0 < c ≤ 4, when a is 1, 2, or 3, b is an integer) and supplying a reaction gas composed of a carbon source gas to one or more second metal oxides and performing heat treatment to produce an undoped composite, and said M is one or more metals selected from Groups 2 to 13, 15, and 16 of the Periodic Table of the Elements.

[0129] The carbon source gas is a compound represented by the following Chemical Formula 7 or one or more mixed gases selected from the group consisting of a compound represented by the following Chemical Formula 7, a compound represented by the following Chemical Formula 8, and an oxygen-containing gas represented by the following Chemical Formula 9.

[0130] <Chemical Formula 7> CnH (2n+2-a) [OH] a

[0131] In the above Chemical Formula 7, n is from 1 to 20, and a is 0 or 1;

[0132] <Chemical Formula 8> CnH 2n

[0133] In the above Chemical Formula 8, n is from 2 to 6;

[0134] <Chemical Formula 9> C x H y O z

[0135] In the above Chemical Formula 9, x is 0 or an integer from 1 to 20, y is 0 or an integer from 1 to 20, and z is 1 or 2.

[0136] The compound represented by Chemical Formula 7 and the compound represented by Chemical Formula 8 are one or more selected from the group consisting of methane, ethylene, propylene, methanol, ethanol, and propanol. The oxygen-containing gas represented by Chemical Formula 9 includes, for example, carbon dioxide (CO2), carbon monoxide (CO), water vapor (H2O), or a mixture thereof.

[0137] M a O c After supplying a reaction gas composed of a carbon source gas to a second metal oxide represented by (0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, c is an integer) and performing a heat treatment, a cooling step using one or more inert gases selected from the group consisting of nitrogen, helium, and argon is further performed. The cooling step means a step of adjusting to normal temperature (20 - 25°C). The carbon source gas may include one or more inert gases selected from the group consisting of nitrogen, helium, and argon.

[0138] In the method for manufacturing a composite, the growth process of a carbon-based material, such as graphene, by a gas-phase reaction can be carried out under various conditions.

[0139] According to the first condition, for example, M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, then c is an integer), first supply methane to the reactor in which the second metal oxide is disposed, and perform a temperature-raising treatment to the heat treatment temperature T. The temperature-raising time to the heat treatment temperature T is 10 minutes to 4 hours, and the heat treatment temperature T is in the range of 700 to 1100 °C. During the reaction time at the heat treatment temperature T, perform the heat treatment. The reaction time is, for example, 4 to 8 hours. Cool the heat-treated product to room temperature to manufacture the composite. The required time for the cooling process from the heat treatment temperature T to room temperature is, for example, 1 to 5 hours.

[0140] According to the second condition, for example, M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, then c is an integer), first supply hydrogen to the reactor in which the second metal oxide is disposed, and perform a temperature-raising treatment to the heat treatment temperature T. The temperature-raising time to the heat treatment temperature T is 10 minutes to 4 hours, and the heat treatment temperature T is in the range of 700 to 1100 °C. After performing the heat treatment for a certain reaction time at the heat treatment temperature T, supply methane gas, and perform the heat treatment during the remaining reaction time. The reaction time is, for example, 4 to 8 hours. Cool the heat-treated product to room temperature to manufacture the composite. Supply nitrogen during the cooling process. The required time for the cooling process from the heat treatment temperature T to room temperature is, for example, 1 to 5 hours.

[0141] According to the third condition, for example, M a O cHydrogen is first supplied to a reactor in which a second metal oxide represented by (0 < a ≤ 3, 0 < c ≤ 4, and if a is 1, 2, or 3, c is an integer) is disposed, and the temperature is raised to a heat treatment temperature T. The temperature rise time to the heat treatment temperature T is 10 minutes to 4 hours, and the heat treatment temperature T is in the range of 700 to 1100 °C. After heat treatment for a certain reaction time at the heat treatment temperature T, a mixed gas of methane and hydrogen is supplied, and heat treatment is carried out during the remaining reaction time. The reaction time is, for example, 4 to 8 hours. The heat-treated product is cooled to room temperature to produce a composite. Nitrogen is supplied during the cooling process. The required time for the cooling process from the heat treatment temperature T to room temperature is, for example, 1 to 5 hours.

[0142] In the process of producing the composite, when the carbon source gas contains water vapor, a composite having very excellent conductivity can be obtained. The content of water vapor in the gas mixture is not limited, and is, for example, 0.01 to 10% by volume based on 100% by volume of the entire carbon source gas. The carbon source gas is, for example, methane, a gas mixture containing methane and an inert gas, or a gas mixture containing methane and an oxygen-containing gas.

[0143] The carbon source gas is also, for example, methane, a gas mixture of methane and carbon dioxide, or a gas mixture of methane, carbon dioxide, and water vapor. In the gas mixture of methane and carbon dioxide, the molar ratio of methane to carbon dioxide is about 1:0.20 to 1:0.50, about 1:0.25 to 1:0.45, or about 1:0.30 to 1:0.40. In the gas mixture of methane, carbon dioxide, and water vapor, the molar ratio of methane to carbon dioxide to water vapor is about 1:0.20 to 0.50:0.01 to 1.45, about 1:0.25 to 0.45:0.10 to 1.35, or about 1:0.30 to 0.40:0.50 to 1.0.

[0144] The carbon source gas is, for example, carbon monoxide or carbon dioxide. The carbon source gas is, for example, a mixed gas of methane and nitrogen. In the mixed gas of methane and nitrogen, the molar ratio of methane to nitrogen is about 1:0.20 to 1:0.50, about 1:0.25 to 1:0.45, or about 1:0.30 to 1:0.40. The carbon source gas may not contain an inert gas such as nitrogen.

[0145] The heat treatment pressure can be selected in consideration of the heat treatment temperature, the composition of the gas mixture, the desired amount of carbon coating, etc. The heat treatment pressure can be controlled by adjusting the amount of the inflowing gas mixture and the amount of the outflowing gas mixture. The heat treatment pressure is, for example, 0.5 atm or more, 1 atm or more, 2 atm or more, 3 atm or more, 4 atm or more, or 5 atm or more.

[0146] The heat treatment time is not particularly limited and can be appropriately adjusted according to the heat treatment temperature, the pressure during heat treatment, the composition of the gas mixture, and the desired amount of carbon coating. For example, the reaction time at the heat treatment temperature is, for example, 10 minutes to 100 hours, 30 to 90 hours, or 50 minutes to 40 hours. For example, as the heat treatment time increases, the amount of carbon deposited, for example, the amount of graphene (carbon), increases, and thereby the electrical properties of the composite can be improved. However, such a tendency is not necessarily directly proportional to the time. For example, after a predetermined time has elapsed, no further carbon deposition, for example, graphene deposition, occurs or the deposition rate decreases.

[0147] Even at a relatively low temperature through the gas-phase reaction of the above-described carbon source gas, M a O c (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, then c is an integer), and M a O b (0 < a ≤ 3, 0 < b < 4, a is 1, 2, or 3, and b is not an integer), by providing a uniform carbon-based material coating, for example, a graphene coating, on one or more selected from the first metal oxides represented thereby, an undoped composite is obtained.

[0148] The undoped composite includes, for example, a matrix of a carbon-based material having one or more structures selected from a spherical structure, a spiral structure in which a plurality of spherical structures are connected, a cluster structure in which a plurality of spherical structures are aggregated, and a sponge structure, such as a graphene matrix, and M disposed within the graphene matrix a O b a first metal oxide represented by (0 < a ≤ 3, 0 < b < 4, a is 1, 2, or 3, and b is not an integer), and M a O c and includes one or more selected from a second metal oxide represented by (0 < a ≤ 3, 0 < c ≤ 4, if a is 1, 2, or 3, c is an integer).

[0149] Next, the first lithium transition metal oxide and the composite are mechanically milled to produce a first core / shell structure. A noble mixer or the like can be used during milling. The rotation speed of the mixer during milling is, for example, 1000 rpm to 2500 rpm. If the milling speed is less than 1000 rpm, the shear force applied to the first lithium transition metal oxide and the composite is weak, so it is difficult for the first lithium transition metal oxide and the composite to form a chemical bond. If the milling speed is excessively high, the complexation proceeds excessively in a short time, making it difficult for the composite to uniformly coat the first lithium transition metal oxide to form a uniform and continuous shell. The milling time is, for example, 5 minutes to 100 minutes, 5 minutes to 60 minutes, or 5 minutes to 30 minutes. If the milling time is excessively short, it is difficult for the composite to uniformly coat the first lithium transition metal oxide to form a uniform and continuous shell.

[0150] If the milling time is too long, the production efficiency may decrease. The content of the composite is 3 wt% or less, 2 wt% or less, or 1 wt% or less of the total weight of the first lithium transition metal oxide and the composite. The content of the composite is, for example, 0.01 to 3 wt%, 0.1 to 2 wt%, or 0.1 to 1 wt% of the total weight of the first lithium transition metal oxide and the composite. For example, the content of the composite is 0.01 to 3 parts by weight, 0.1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 parts by weight, based on 100 parts by weight of the mixture of the first lithium transition metal oxide and the composite. The average particle size (D50) of the composite used in the mechanical milling of the first lithium transition metal oxide and the composite is, for example, 1 μm to 20 μm, 3 μm to 15 μm, or 5 μm to 10 μm.

[0151] Alternatively, the second lithium transition metal oxide and the composite are mechanically milled to prepare a second core / shell structure, which is prepared in the same manner as the first core / shell structure, except that the second lithium transition metal oxide is used instead of the first lithium transition metal oxide.

[0152] Alternatively, the first core / shell structure and the second core / shell structure are each produced by the method described above.

[0153] The first core / shell structure and the second lithium metal oxide are then mixed to produce a composite positive electrode active material. The first core / shell structure and the second lithium transition metal oxide are mixed in a weight ratio of, for example, 90:10 to 60:40, 85:15 to 65:35, or 80:20 to 70:30. When the first core / shell structure and the second lithium transition metal oxide have a weight ratio in such a range, the energy density and / or cycle characteristics of a lithium battery including the composite positive electrode active material can be further improved.

[0154] Alternatively, a composite positive electrode active material is produced by mixing a first lithium transition metal oxide and a second core / shell structure. The mixing of the first lithium transition metal oxide and the second core / shell structure is also, for example, in a weight ratio of 90:10 to 60:40, 85:15 to 65:35, or 80:20 to 70:30. By having such a weight ratio range for the first lithium transition metal oxide and the second core / shell structure, the energy density and / or cycle characteristics of a lithium battery including the composite positive electrode active material can be further improved.

[0155] Alternatively, a composite positive electrode active material is produced by mixing a first core / shell structure and a second core / shell structure. The mixing of the first core / shell structure and the second core / shell structure is also, for example, in a weight ratio of 90:10 to 60:40, 85:15 to 65:35, or 80:20 to 70:30. By having such a weight ratio range for the first core / shell structure and the second core / shell structure, the energy density and / or cycle characteristics of a lithium battery including the composite positive electrode active material can be further improved.

[0156] The present invention will be described in more detail through the following examples and comparative examples. However, the examples are merely illustrative of the present invention and do not limit the scope of the present invention.

[0157] (Production of Composite) Production Example 1: Al2O3@Gr Composite

[0158] After placing Al2O3 particles (average particle size: about 20 nm) in the reactor, the internal temperature of the reactor was raised to 1000 °C under the condition that CH4 was supplied at about 300 sccm for about 30 minutes at 1 atm in the reactor.

[0159] Then, after performing heat treatment by holding at the temperature for 7 hours, the internal temperature of the reactor was adjusted to room temperature (20 to 25 °C) to obtain an undoped composite in which Al2O3 particles and Al2O z (0 < z < 3) particles were embedded in graphene.

[0160] The alumina content contained in the undoped composite was 60 wt%.

[0161] Comparative Production Example 1: SiO2@Gr composite

[0162] After positioning SiO2 particles (average particle size: about 15 nm) in the reactor, the internal temperature of the reactor was raised to 1000 °C under the condition that CH4 was supplied at about 300 sccm for about 30 minutes at 1 atm in the reactor.

[0163] Next, after performing heat treatment by holding at the above temperature for 7 hours, the internal temperature of the reactor was adjusted to room temperature (20 - 25 °C) to obtain a composite in which SiO2 particles and SiO y (0 < y < 2) particles were embedded in graphene.

[0164] (Production of composite cathode active material) Example 1: Al2O3@Gr composite 0.4 wt% (alumina 0.24 wt%) - coated large - diameter NCA91 and Al2O3@Gr composite 0.4 wt% (alumina 0.24 wt%) - coated small - diameter NCA91

[0165] Large - diameter LiNi with an average particle size of 17 μm 0.91 Co 0.05 Al 0.04 O2 (hereinafter referred to as large - diameter NCA91) and the composite prepared in Production Example 1 were milled at a rotational speed of about 1000 - 2000 rpm for about 5 - 30 minutes using a Nobilta Mixer (Hosokawa, Japan) to obtain a first core / shell structure. The mixing weight ratio of large - diameter NCA and the composite obtained in Production Example 1 was 99.6:0.4.

[0166] Small - diameter LiNi with an average particle size of 3.5 μm 0.91 Co 0.05 Al 0.04O2 (hereinafter referred to as small diameter NCA 91) and the composite prepared in Preparation Example 1 were milled for about 5 to 30 minutes at a rotation speed of about 1000 to 2000 rpm using a Nobilta Mixer (Hosokawa, Japan) to obtain a second core / shell structure. The mixing weight ratio of the small diameter NCA and the composite obtained in Preparation Example 1 was 99.6:0.4.

[0167] The first core / shell structure and the second core / shell structure were mixed in a weight ratio of 7:3 to prepare a composite positive electrode active material.

[0168] The particle size distribution was measured using a particle size analyzer (PSA) and it was found to have a bimodal particle size distribution.

[0169] Example 2: Large diameter NCA91 coated with Al2O3@Gr composite 0.4wt% (alumina 0.24wt%) and bare small diameter NCA91

[0170] Large-diameter LiNi with an average particle size of 17 μm 0.91 Co 0.05 Al 0.04 O2 (hereinafter referred to as large diameter NCA 91) and the composite prepared in Production Example 1 were milled for about 5 to 30 minutes at a rotation speed of about 1000 to 2000 rpm using a Nobilta Mixer (Hosokawa, Japan) to obtain a first core / shell structure. The mixing weight ratio of the large diameter NCA and the composite obtained in Production Example 1 was 99.6:0.4.

[0171] Small diameter LiNi with an average particle size of 3.5 μm 0.91 Co 0.05 Al 0.04 O2 (hereafter referred to as small diameter NCA91) was used as is.

[0172] The first core / shell structure and the small diameter NCA were mixed in a weight ratio of 7:3 to prepare a composite positive electrode active material.

[0173] The particle size distribution was measured using a particle size analyzer (PSA) and it was found to have a bimodal particle size distribution.

[0174] Example 3: Bare large-diameter NCA91 and small-diameter NCA91 coated with 0.4 wt% Al2O3@Gr composite (0.24 wt% alumina)

[0175] Large-diameter LiNi with an average particle size of 17 μm 0.91 Co 0.05 Al 0.04 O2 (hereafter referred to as large-diameter NCA91) was used as is.

[0176] Small diameter LiNi with an average particle size of 3.5 μm 0.91 Co 0.05 Al 0.04 O2 (hereinafter referred to as small diameter NCA 91) and the composite prepared in Preparation Example 1 were milled for about 5 to 30 minutes at a rotation speed of about 1000 to 2000 rpm using a Nobilta Mixer (Hosokawa, Japan) to obtain a second core / shell structure. The mixing weight ratio of the small diameter NCA and the composite obtained in Preparation Example 1 was 99.6:0.4.

[0177] The large-diameter NCA and the second core / shell structure were mixed in a weight ratio of 7:3 to prepare a composite positive electrode active material.

[0178] The particle size distribution was measured using a particle size analyzer (PSA) and it was found to have a bimodal particle size distribution.

[0179] Comparative Example 1: Bare large diameter NCA91 alone

[0180] The large-diameter NCA with an average particle size of 17 μm was used as it was as a composite positive electrode active material.

[0181] The particle size distribution was measured using a particle size analyzer (PSA) and it was confirmed that the particle size distribution was monomodal.

[0182] Comparative Example 2: Large-diameter NCA91 coated with 0.4 wt% SiO2@Gr composite (0.24 wt% silica) and: Small-diameter NCA91 coated with 0.4 wt% SiO2@Gr composite (0.24 wt% silica)

[0183] A composite positive electrode active material was prepared in the same manner as in Example 1, except that the SiO2@Gr composite prepared in Comparative Preparation Example 1 was used instead of the Al2O3@Gr composite prepared in Preparation Example 1.

[0184] (Lithium battery (half cell) manufacturing) Example 4 (Production of positive electrodes) The composite positive electrode active material prepared in Example 1, a carbon conductive material (Denka Black), and polyvinylidene fluoride (PVdF) were mixed in a weight ratio of 96:2:2, and then mixed with N-methylpyrrolidone (NMP) in an agate mortar to prepare a slurry.

[0185] The slurry was bar coated on an aluminum collector having a thickness of 15 μm, dried at room temperature, and then dried again under vacuum at 120° C., followed by rolling and punching to prepare a positive electrode plate having a thickness of 60 μm.

[0186] (Coin cell manufacturing) Using the positive electrode prepared above, lithium metal was used as the counter electrode, a PTFE separator, and a solution of 1.15M LiPF6 dissolved in EC (ethylene carbonate) + EMC (ethyl methyl carbonate) + DMC (dimethyl carbonate) (volume ratio 2:4:4) was used as the electrolyte to prepare coin cells.

[0187] Examples 5 to 6 Coin cells were prepared in the same manner as in Example 4, except that the composite positive electrode active materials prepared in Examples 2 and 3 were used instead of the composite positive electrode active material prepared in Example 1.

[0188] Comparative Examples 3 to 4 A coin cell was manufactured in the same manner as in Example 4, except that the composite positive electrode active materials prepared in Comparative Examples 1 and 2 were used instead of the composite positive electrode active material manufactured in Example 1, respectively.

[0189] Evaluation Example 1: XPS Spectrum Evaluation

[0190] During the manufacturing process of the undoped composite manufactured in Production Example 1, XPS spectra were measured using Quantum 2000 (Physical Electronics) over time. The XPS spectra of the C 1s orbital and the Al 2p orbital for the samples before heating, after 1 minute, after 5 minutes, after 30 minutes, after 1 hour, and after 4 hours were measured, respectively. At the initial stage of heating, only a peak for the Al 2p orbital was shown, and no peak for the C 1s orbital was shown.

[0191] After 30 minutes, a peak for the C 1s orbital was clearly shown, and the magnitude of the peak for the Al 2p orbital decreased significantly.

[0192] After 30 minutes, a peak for the C 1s orbital due to C-C bonds and C=C bonds resulting from the growth of graphene was clearly shown near 284.5 eV.

[0193] As the reaction time elapsed, the oxidation number of aluminum decreased, and the peak position of the Al 2p orbital shifted to the side with a lower binding energy (eV).

[0194] Therefore, as the reaction proceeded, graphene grew on the Al2O3 particles, and it was confirmed that Al2O x (0 < x < 3) was generated.

[0195] The average contents of carbon and aluminum were measured through XPS analysis of 10 regions of the composite sample produced in Reference Production Example 1. The deviation of the aluminum content for each region was calculated with respect to the measurement results. The deviation of the aluminum content was expressed as a percentage with respect to the average value, and this was referred to as the uniformity. The percentage with respect to the average value of the deviation of the aluminum content, that is, the uniformity of the aluminum content, was 1%. Therefore, it was confirmed that alumina was uniformly distributed within the composite produced in Reference Production Example 1.

[0196] Evaluation Example 2: SEM, HR-TEM and SEM-EDAX Analyses

[0197] Scanning electron microscopy, high-resolution transmission electron microscopy and EDAX analysis were performed on the composite produced in Production Example 1, the composite positive electrode active material produced in Example 1, and the bare NCA of Comparative Example 1.

[0198] FEI Titan80-300 from Philips was used during SEM-EDAX analysis.

[0199] The composite produced in Production Example 1 was shown to have a structure in which Al2O3 particles and Al2O z (0 < z < 3) particles were embedded in graphene. It was confirmed that a graphene layer was disposed on the outer contour of one or more particles selected from among Al2O3 particles and Al2O z (0 < z < 3). One or more of the Al2O3 particles and Al2O z (0 < z < 3) particles selected therefrom were uniformly dispersed within the graphene matrix. One or more of the particle sizes of the Al2O3 particles and Al2O z (0 < z < 3) particles were about 20 nm. The particle size of the composite produced in Production Example 1 was about 100 nm to 200 nm.

[0200] In the composite positive electrode active material produced in Example 1, it was confirmed that a shell formed by a composite containing graphene was disposed on the NCA core.

[0201] SEM-EDAX analysis was performed on the bare NCA of Comparative Example 1 and the composite positive electrode active material prepared in Example 1.

[0202] It was confirmed that the concentration of aluminum (Al) distributed on the surface of the composite positive electrode active material of Example 1 was increased compared to that of the bare NCA composite positive electrode active material of Comparative Example 1.

[0203] Therefore, it was confirmed that in the composite positive electrode active material of Example 1, the composite prepared in Preparation Example 1 was uniformly coated on the NCA core to form a shell.

[0204] Evaluation example 3: Pellet density measurement

[0205] The pellet densities of the composite positive electrode active materials prepared in Examples 1 to 3 and Comparative Example 1 were measured, and the results are shown in Table 1 below.

[0206] 1 g of the positive electrode active material prepared in Examples 1 to 3 and Comparative Example 1 was placed in a circular mold having a diameter of 1 cm, and subjected to a pressure of 1000 kgf / cm 2 The density was measured as the mass per volume of the positive electrode active material having a pellet shape obtained by applying pressure.

[0207] [Table 1]

[0208] As shown in Table 1, the composite positive electrode active materials of Examples 1 to 3 having a bimodal particle size distribution had increased pellet density compared to the composite positive electrode active material of Comparative Example 1 having a monomodal particle size distribution.

[0209] Therefore, it was confirmed that the lithium batteries including the composite positive electrode active materials of Examples 1 to 3 provided improved energy density compared to the lithium battery including the composite positive electrode active material of Comparative Example 1.

[0210] Evaluation example 4: Charge / discharge characteristic evaluation at room temperature (25°C)

[0211] The lithium batteries prepared in Examples 4 to 6 and Comparative Examples 3 to 4 were charged at a constant current of 0.1 C rate at 25° C. until the voltage reached 4.4 V (vs. Li), and then cut off at a current of 0.05 C rate while maintaining 4.4 V in constant voltage mode. Then, the batteries were discharged at a constant current of 0.1 C rate until the voltage reached 2.8 V (vs. Li) during discharge (formation cycle).

[0212] The lithium battery that had undergone the chemical cycle was charged at a constant current of 0.2C rate at 25°C until the voltage reached 4.4V (vs. Li), and then cut-off at a current of 0.05C rate while maintaining 4.4V in constant voltage mode. It was then discharged at a constant current of 0.2C rate until the voltage reached 2.8V (vs. Li) (first cycle). Such cycles were repeated under the same conditions up to the 50th cycle (50 repetitions).

[0213] In all charge / discharge cycles, a 10-minute rest period was allowed after one charge / discharge cycle. Some of the results of the room temperature charge / discharge experiments are shown in Table 1 below. The initial efficiency is defined by the following Equation 1, and the capacity retention rate is defined by the following Equation 2.

[0214] <Formula 1> Initial efficiency [%] = [discharge capacity at 1st cycle / charge capacity at 1st cycle] x 100

[0215] <Formula 2> Capacity retention rate [%] = [discharge capacity at 50th cycle / discharge capacity at 1st cycle] x 100

[0216] Evaluation example 5: Evaluation of direct current internal resistance (DC-IR) before and after charging and discharging at room temperature

[0217] For the lithium batteries prepared in Examples 4 to 6 and Comparative Examples 3 and 4, the direct current internal resistance (DC-IR) was measured before and after the room temperature charge-discharge evaluation by the following method.

[0218] In the first cycle, charge the battery to a voltage of 50% SOC (state of charge) at a current of 0.5C, then cut off at 0.02C and rest for 10 minutes. Discharge at a constant current of 0.5C for 30 seconds, then rest for 30 seconds, charge at a constant current of 0.5C for 30 seconds, rest for 10 minutes, Discharge at a constant current of 1.0C for 30 seconds, then rest for 30 seconds, charge at a constant current of 0.5C for 1 minute, then rest for 10 minutes, Discharge at a constant current of 2.0C for 30 seconds, then rest for 30 seconds, charge at a constant current of 0.5C for 2 minutes, then rest for 10 minutes, The battery was discharged at a constant current of 3.0 C for 30 seconds, then rested for 30 seconds, charged at a constant current of 0.5 C for 3 minutes, and rested for 10 minutes.

[0219] The DC internal resistance (DC-IR, R = ΔV / ΔI) was calculated from the ratio of the average voltage change (ΔV) and the average current change (ΔI) during constant current discharge at each C-rate, and the average value was taken as the measured value.

[0220] Some of the measured DC internal resistances before the high-temperature charge-discharge evaluation and after the room-temperature charge-discharge evaluation are shown in Table 2 below.

[0221] [Table 2]

[0222] As shown in Table 2, the lithium batteries of Examples 4 to 6 had improved initial efficiency and room temperature life characteristics compared to the lithium battery of Comparative Example 3.

[0223] Although not shown in the table, the lithium battery of Comparative Example 4 was also inferior to the lithium batteries of Examples 4 to 6 in room temperature life characteristics.

[0224] Moreover, in the lithium batteries of Examples 4 to 6, the increase in the direct current internal resistance after charge / discharge at room temperature was significantly suppressed compared to the lithium battery of Comparative Example 3.

[0225] Evaluation example 6: High temperature (45℃ charge / discharge characteristic evaluation)

[0226] The lithium batteries prepared in Examples 4 to 6 and Comparative Examples 3 to 4 were charged at a constant current of 0.2 C rate at 25° C. until the voltage reached 4.4 V (vs. Li), and then cut off at a current of 0.05 C rate while maintaining 4.4 V in constant voltage mode. Then, the batteries were discharged at a constant current of 0.2 C rate until the voltage reached 2.8 V (vs. Li) during discharge (formation cycle).

[0227] The lithium battery that had undergone the chemical cycle was charged at a constant current of 0.2C rate at 45°C until the voltage reached 4.4V (vs. Li), and then cut off at a current of 0.05C rate while maintaining 4.4V in constant voltage mode. It was then discharged at a constant current of 0.2C rate until the voltage reached 2.8V (vs. Li) (first cycle). This cycle was repeated under the same conditions up to the 100th cycle (100 repetitions).

[0228] In all charge / discharge cycles, a 10-minute rest period was allowed after one charge / discharge cycle.

[0229] Some of the results of the high temperature charge-discharge experiment are shown in Table 3. The capacity retention rate is defined by the following Equation 3.

[0230] <Formula 3> Capacity retention rate [%] = [discharge capacity at 100th cycle / discharge capacity at 1st cycle] x 100

[0231] [Table 3]

[0232] As shown in Table 3, the lithium batteries of Examples 4 to 6 had improved high-temperature life characteristics compared to the lithium battery of Comparative Example 3.

[0233] Although not shown in Table 3, the high-temperature life characteristics of the lithium battery of Comparative Example 4 were significantly deteriorated compared to the lithium batteries of Examples 4 to 6. [Industrial Applicability]

[0234] According to one aspect, the composite positive electrode active material has a shell including a first metal oxide and a carbon-based material disposed on one or more cores of a large-diameter lithium transition metal oxide and a small-diameter lithium transition metal oxide, thereby improving the high-temperature cycle characteristics of a lithium battery and suppressing an increase in internal resistance.

Claims

1. a first core comprising a first lithium transition metal oxide; a second core comprising a second lithium transition metal oxide; a shell disposed along a surface of at least one of the first core and the second core; The shell has the formula M a O b (0<a≦3, 0<b<4, and if a is 1, 2, or 3, then b is not an integer), and a carbon-based material, The first metal oxide is disposed in a carbon-based material matrix, and the M is one or more metals selected from Groups 2 to 13, 15, and 16 of the Periodic Table of Elements; the first lithium transition metal oxide and the second lithium transition metal oxide have different average particle sizes.

2. 2. The composite positive electrode active material of claim 1, wherein the first lithium transition metal oxide is a large-diameter lithium transition metal oxide, and the particle size of the first lithium transition metal oxide is large and larger than the particle size of the second lithium transition metal oxide.

3. 2. The composite active cathode material of claim 1, wherein the first lithium transition metal oxide and the second lithium transition metal oxide have a bimodal particle size distribution.

4. 2. The composite positive electrode active material of claim 1, wherein the first lithium transition metal oxide has an average particle size of more than 10 μm to 25 μm, and the second lithium transition metal oxide has an average particle size of 1 μm to 10 μm.

5. 2. The composite positive electrode active material of claim 1, wherein a weight ratio of the first lithium transition metal oxide to the second lithium transition metal oxide is from 90:10 to 60:

40.

6. the shell is disposed only on the first core, the shell is disposed only on the second core; or The composite positive electrode active material of claim 1 , wherein the shell is disposed on both the first core and the second core.

7. 2. The composite positive electrode active material of claim 1, wherein the metal contained in the first metal oxide is one or more metals selected from the group consisting of Al, Nb, Mg, Sc, Ti, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, Sb, and Se.

8. The first metal oxide is Al 2 O z (0<z<3), NbO x (0<x<2.5), MgO x (0<x<1), Sc 2 O z (0<z<3), TiO y (0<y<2), ZrO y (0<y<2), V 2 O z (0<z<3), WO y (0<y<2), MnO y (0<y<2), Fe 2 O z (0<z<3), Co 3 O w (0<w<4), PdO x (0<x<1), CuO x (0<x<1), AgO x (0<x<1), ZnO x (0<x<1), Sb 2 O z (0<z<3), and SeO y 2. The composite positive electrode active material of claim 1 , wherein y is one or more selected from the group consisting of (0<y<2).

9. The shell has the formula M a O c (0<a≦3, 0<c≦4, and if a is 1, 2, or 3, then c is an integer), the second metal oxide comprises the same metal as the first metal oxide; 2. The composite positive electrode active material of claim 1, wherein a ratio of a to c, c / a, of the second metal oxide is greater than a ratio of a to b, b / a, of the first metal oxide.

10. The second metal oxide is Al 2 O 3 , NbO, NbO 2 , Nb 2 O 5 , MgO, Sc 2 O 3 , TiO 2 , ZrO 2 , V 2 O 3 , W.O. 2 , MnO 2 , Fe 2 O 3 , Co 3 O 4 , PdO, CuO, AgO, ZnO, Sb 2 O 3 , and SeO 2 and the first metal oxide is a reduction product of the second metal oxide.

11. 2. The composite cathode active material of claim 1, wherein the shell has a thickness of 1 nm to 5 μm.

12. the shell comprises at least one selected from the group consisting of a composite including the first metal oxide and a carbon-based material and a milling result of the composite, 2 . The composite positive electrode active material of claim 1 , wherein the content of at least one selected from the group consisting of the composite and the milled product of the composite is 3 wt % or less of a total weight of the composite positive electrode active material.

13. the composite further comprises a second metal oxide having a different composition than the first metal oxide; At least one of the first metal oxide and the second metal oxide has an average particle size of 1 nm to 1 μm; The composite positive electrode active material of claim 12 , wherein the uniformity deviation of at least one selected from the first metal oxide and the second metal oxide is 3% or less.

14. the carbon-based material has a branched structure, and the first metal oxide is distributed within the branched structure; 13. The composite active cathode material of claim 12, wherein the branched structure comprises a plurality of particles of carbon-based material in contact with one another.

15. the carbon-based material has at least one structure selected from a spherical structure, a spiral structure in which the spherical structures are connected, and a cluster structure in which the spherical structures are aggregated, the first metal oxide is distributed within the spherical structures, the spherical structures have a size of 50 nm to 300 nm, the spiral structures have a size of 500 nm to 100 μm, and the cluster structures have a size of 0.5 mm to 10 cm; The composite is a wrinkled faceted-ball structure or a planar structure, and at least one selected from a first metal oxide and a second metal oxide is distributed inside or on a surface of the faceted-ball structure or the planar structure; 13. The composite active cathode material of claim 12, wherein the carbonaceous material extends a distance of 10 nm or less in the first metal oxide and comprises at least 1-20 layers of carbonaceous material, the total thickness of the carbonaceous material being between 0.6 nm and 12 nm.

16. 2. The composite positive electrode active material of claim 1, wherein the first lithium transition metal oxide and / or the second lithium transition metal oxide is represented by any one of the following Formulas 1 to 5: <Chemical formula 1> Li a Ni x Co y M z O 2-b A b In the above Chemical Formula 1, 1.0≦a≦1.2, 0≦b≦0.2, 0.8≦x<1, 0<y≦0.3, 0<z≦0.3, and x+y+z=1; M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof; A is F, S, Cl, Br or a combination thereof; <Chemical formula 2> L)) x Co y Mn z O 2 <Chemical formula 3> L)) x Co y Al z O 2 In the formulas 2 and 3, 0.8≦x≦0.95, 0<y≦0.2, 0<z≦0.2, and x+y+z=1; <Chemical formula 4> L)) x Co y Mn z Al w O 2 In the formula 4, 0.8≦x≦0.95, 0<y≦0.2, 0<z≦0.2, 0<w≦0.2, and x+y+z+w=1; <Chemical formula 5> Li a Co x MyO 2-b A b In the above Chemical Formula 5, 1.0≦a≦1.2, 0≦b≦0.2, 0.9≦x≦1, 0≦y≦0.1, and x+y=1; M is manganese (Mn), niobium (Nb), vanadium (V), magnesium (Mg), gallium (Ga), silicon (Si), tungsten (W), molybdenum (Mo), iron (Fe), chromium (Cr), copper (Cu), zinc (Zn), titanium (Ti), aluminum (Al), boron (B), or a combination thereof; A is F, S, Cl, Br or a combination thereof.

17. A positive electrode comprising the composite positive electrode active material of any one of claims 1 to 16.

18. The positive electrode according to claim 17 ; A negative electrode; a lithium battery comprising an electrolyte disposed between the positive electrode and the negative electrode.

19. providing a first lithium transition metal oxide; providing a second lithium transition metal oxide; Providing a complex; preparing at least one of a first core / shell structure obtained by mechanically milling the first lithium transition metal oxide and the composite and a second core / shell structure obtained by mechanically milling the second lithium transition metal oxide and the composite; mixing the first core / shell structure with the second lithium transition metal oxide, mixing the second core / shell structure with the first lithium transition metal oxide, or mixing the first core / shell structure with the second core / shell structure; The complex has the formula M a O b (0<a≦3, 0<b<4, and if a is 1, 2, or 3, then b is not an integer), and a carbon-based material, the first metal oxide is disposed in a carbon-based material matrix, and M is one or more metals selected from Groups 2 to 13, 15, and 16 of the Periodic Table of Elements.

20. providing the complex, M a O c (0<a≦3, 0<c≦4, if a is 1, 2, or 3, c is an integer) and a reaction gas comprising a carbon source gas is supplied to the one or more second metal oxides, 20. The method of claim 19, wherein M is at least one metal selected from the group consisting of metals in Groups 2 to 13, 15, and 16 of the Periodic Table.

Citation Information

Patent Citations

  • Positive electrode active material for lithium ion secondary battery, and method for manufacturing the same

    JP2012169217A

  • Nonaqueous electrolyte secondary battery

    JP2013077421A

  • Lithium nickel cobalt aluminum oxide composite positive electrode material, method for producing the same, and lithium ion secondary battery

    JP2015130340A

  • Method for manufacturing lithium ion secondary battery

    JP2015170476A

  • Cathode material for secondary batteries and lithium secondary batteries containing the same

    JP2020537316A